When kings rode to Delhi - Festing, Gabrielle (New Delhi : Asian Educational Service, 1997)
History of Delhi from 1000 A.D. to 1761 A.D.
Reprint. Originally published: Edinburgh : William Blackwood and Sons, 1912.
Keywords: Delhi (India) -- History; Mogul Empire -- History